"It's about sharing a moment": Parents' views and experiences of home reading with their autistic children with moderate-to-severe intellectual disabilities. (September 2022) - Walker, Rachel; Swain, Jon; Pellicano, Elizabeth
Abstract: Background: The home literacy environment plays a critical role in the development of children's literacy and language development. Little is known, however, about the home literacy environment of autistic children, especially those with moderate-to-severe intellectual disabilities. Aims: The current study used a sequential mixed-methods design to understand how parents attempt to engage their autistic children in reading activities and support them in learning to read. Methods and procedure: First, 63 parents (53 mothers) whose autistic children attended an autism-specific special school completed a bespoke questionnaire about the home literacy environments for their children (n = 69, age range = 3–11 years, 61 boys, 8 girls). Second, a subsample of parents (n = 19, 15 mothers) participated in focus groups to understand in-depth their views and experiences of home reading with their children (n = 20, age range = 3–11 years, 19 boys, 1 girl). We used reflexive thematic analysis to analyse the focus group data. Outcomes and results: Across questionnaire and focus group methods, parents were united in considering reading to be an important life skill, a sentiment that was reflected both by their often literacy-rich homes and the ingenuity in their efforts to engage their children in shared home-reading activities – even when such engagement could be challenging. They also emphasised, however, the importance of valuing these activities as an opportunity to "catch a moment" with their child. Conclusions and implications: Parents and teachers should work together to identify ways to enhance autistic children's engagement in shared home-reading activities, listening to and learning from each other's experiences and expertise, and to show what is possible within each learning context. Highlights: This study examined the home literacy environment of autistic children with intellectual disabilities. We identified the features of families' home literacy environment and parents' experiences of reading with their children. Parents valued spending time reading with their children but found it difficult to engage children. Schools should work together with parents to enhance children's engagement in shared home-reading activities.